Chiari type 1.5 malformation with the right upper limb monoparesis and Horner’s syndrome: A case report (Indian Journal of Case Reports, 2021)
Chiari 1.5 malformation is a rare condition characterized by caudal descent of the brain stem, together with the descent of the cerebellar tonsils. This is a case report of a 36-year-old female who had right upper limb monoparesis and Horner’s syndrome since birth and presented with complaints of vertigo and unsteady gait. On examination, revealed ataxia and nystagmus and magnetic resonance imaging showed Chiari type I.5 malformation with associated mild communicating hydrocephalus, syringobulbia, and syringomyelia.